Non-associated plasticity analysis of slope stability under steady unsaturated flow conditions. (December 2020) - Li, Chengchao; Jiang, Pengming; Zhou, Aizhao
Abstract: This study presents an analytical framework of limit analysis for the ultimate load of unsaturated soil slopes with the non-associated plasticity. The method of characteristics combined with boundary value problems is applied to build the slip line field that satisfies the stress boundary and the velocity boundary simultaneously. According to the proposed approach, a value of the ultimate load of slopes can be directly addressed, which is within the narrow range determined by the upper bound (UB) and the lower bound (LB) solutions. The non-associated Mohr-Coulomb criterion is presented to investigate the effect of the matric suction and the dilation on slope stability. The comparison with the existing methods is conducted to validate the presented solutions. The results indicate that the effect of the flow condition and the dilation on the ultimate load of four types of soil slopes can be estimated accurately by the proposed approach.